Influence of childhood experiences, disclosure and environment on adult adoptees' relationship satistaction - Garcia, Maria Rowena M. (Animo Repository, 2011)
In the attempt to take a constructive approach on the study of adoption, the present study investigates on the influence of childhood experiences, disclosure, and the external environment on the development of Filipino adult adoptees relationship satisfaction. To gather data, a qualitative analysis and descriptive approach was used. Participants consisted of 2 males and 4 females Filipino adult adoptees with ages ranging from 18 to 45 years old. Eleven categories emerged in the results of the data collection under which was further divided into twenty-seven themes. Overall, results showed that adult adoptees consider themselves to be satisfied with their relationships despite their adoption circumstance. Under childhood experiences, their attachment with their adoptive families has strongly influenced their relationship satisfaction during their childhood. In terms of their disclosure status, a good relationship with the adoptive family, proper timing and execution of disclosure and a positive reaction from the adoptee could also influence their satisfaction in relationships. Lastly, influence of external environment specifically with their peers is found to be relevant. Aside from the three aspects, it was discovered that there is a phenomenon on the adoptees blockage of memory and that a five phases of the adoption-reconstruction model can be associated from the results of the present study.